Trends and the associated factors of optimal immunological response and virological response in late anti-retroviral therapy initiation HIV cases in Taiwan from 2009 to 2020 - Chun-Yuan Lee; Yi-Pei Lin; Chun-Yu Lin; Tun-Chieh Chen; Shin-Huei Kuo; Shih-Hao Lo; Sheng-Fan Wang; Po-Liang Lu (Elsevier, 2024)
Background: Late cART initiation (CD4 count ≤200 cells/μL or AIDS-defining opportunistic illnesses [AOIs] at cART initiation) impedes CD4 count recovery and virologic suppression after cART initiation. However, studies to evaluate trends of and modifiable factors for optimal immunological response (IR) and virological response (VR) in people living with HIV (PLWH) with late cART initiation with the current HIV treatment strategies are limited. Methods: We retrospectively identified 475 PLWH with late cART initiation in 2009-2020. Patients were grouped based on the presence of IR (CD4 count ≥200 cells/μL) or VR (plasma viral load [PVL] ≤ 50 copies/mL) within 18 months after cART initiation (403 [84.8%] IR(+) and 72 [15.2%] IR(−); 422 [88.8%] VR(+) and 53 [11.2%] VR(−)). We used Joinpoint regression to identify IR (+) and VR(+) proportion changes. Results: From 2009 to 2020, the proportion of IR(+) patients remained unchanged (75% to 90%, P = 0.102), whereas that of VR(+) patients increased significantly (75% to 95%, P = 0.007). No join point was identified for either IR(+) or VR(+), and the annual percentage change was 0.56% (nonsignificant) and 1.35% (significant) for IR(+) and VR(+), respectively. Compared to IR(−) patients, IR(+) patients were more likely to have a higher pre-cART PVL, to start with a first-line INSTI-based regimen, or to start cART within 14 days of HIV diagnosis but were less likely to have chronic kidney disease, composite AOIs, or a lower pre-cART CD4 count. Compared to VR(−) patients, VR(+) patients were more likely to start a single-tablet regimen but were less likely to have a higher pre-cART PVL. Conclusions: Our study identified several modifiable factors for optimal IR (rapid cART initiation and INSTI-based regimen initiation) and for optimal VR (STR initiation) among late initiators, which may guide early treatment modifications to reduce their AIDS-defining event incidence and mortality.